2017
DOI: 10.1038/ijo.2017.102
|View full text |Cite
|
Sign up to set email alerts
|

Serum vascular cell adhesion molecule-1 predicts significant liver fibrosis in non-alcoholic fatty liver disease

Abstract: VCAM-1 levels are able to accurately predict significant (⩾F2) fibrosis in NAFLD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
28
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 47 publications
11
28
0
2
Order By: Relevance
“…In our dataset, predominantly VCAM‐1 and ICAM‐1 as well as MMP2 and TIMP1 were upregulated by omentin and involved in this pathway. Serum levels of VCAM‐1 and ICAM‐1 are predictors of hepatic fibrosis and hepatocellular carcinoma risk, respectively . Interestingly, the transcriptional activation of TIMP‐1 and MMP‐2 is important for the pathogenesis of liver fibrosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our dataset, predominantly VCAM‐1 and ICAM‐1 as well as MMP2 and TIMP1 were upregulated by omentin and involved in this pathway. Serum levels of VCAM‐1 and ICAM‐1 are predictors of hepatic fibrosis and hepatocellular carcinoma risk, respectively . Interestingly, the transcriptional activation of TIMP‐1 and MMP‐2 is important for the pathogenesis of liver fibrosis .…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of VCAM-1 and ICAM-1 are predictors of hepatic fibrosis and hepatocellular carcinoma risk, respectively. 54,55 Interestingly, the transcriptional activation of TIMP-1 and MMP-2 is important for the pathogenesis of liver fibrosis. 53 The potential link between these pro- Interestingly, the most activated upstream cytokines IL-1β and TNFα regulate the activity of NFκB, and all three classes of MAPK (JNK, ERK1/2, and p38 MAPK).…”
Section: Omentin-regulated Proteins Associated With General Cellulamentioning
confidence: 99%
“…Our group previously demonstrated that blocking VEGF receptor 2 reduces hepatic angiogenesis and attenuates hepatic steatosis and inflammation in a NASH mouse model . In addition, we have recently reported elevated vascular cell adhesion molecule 1 (VCAM‐1) serum levels in NAFLD patients, which might have clinical utility as a biomarker for the diagnosis of significant fibrosis . However, although VEGF and multiple tyrosine kinase inhibitors can successfully counteract angiogenesis in models of chronic liver disease, their clinical use might be limited by their potentially severe side effects, especially in a setting requiring chronic administration.…”
mentioning
confidence: 99%
“…(8) In addition, we have recently reported elevated vascular cell adhesion molecule 1 (VCAM-1) serum levels in NAFLD patients, which might have clinical utility as a biomarker for the diagnosis of significant fibrosis. (9) However, although VEGF and multiple tyrosine kinase inhibitors can successfully counteract angiogenesis in models of chronic liver disease, (8,10,11) their clinical use might be limited by their potentially severe side effects, especially in a setting requiring chronic administration. Moreover, vascular alterations resulting from angiogenesis and endothelial dysfunction also promote monocyte infiltration, which in turn fuels NASH progression and stimulates angiogenesis.…”
mentioning
confidence: 99%
“…У свою чергу, активація тромбоцитів пов'язана з ендоте-ліальною дисфункцією та в подальшому -з ремо-делюванням судинної стінки [2]. Зокрема, збіль-шення рівня молекул адгезії сприяє проникненню лейкоцитів у судинну стінку та накопиченню в ній ліпідів, що відображає ступінь пошкодження ендо-теліальних клітин і порушення мікроциркуляції в тканинах [9,17]. Це викликає розвиток ендотеліаль-ної дисфункції, яка вважається одним із чинників розвитку ІХС.…”
unclassified